OPTIMALISASI PERAN DANTON DALAM MEMINIMALISIR PELANGGARAN PRAJURIT BATALYON INFANTERI 405/ SURYA KUSUMA - Martono, Agus Djoko; Putro, Harjono Pamungkas; Prasetyo, Heru; Mega, Aryanti (PPM Sdirjianbang Akademi Militer, 2023)
Leaders are individuals who are accepted by others without having violence. A platoon commander who brings his members without fierceness and uses maturity and family members’ methods has made the members feel close to him because of his sense of responsibility. The purpose of this research is to know the role, the obstacle and the effort faced by a platoon commander to minimize the discipline offenses of the soldiers in battalion 405 / Surya Kusuma.The method used in this study is a qualitative method to describe the role of platoon commanders in 405 / Kusuma. From the analysis and discussion, the role of platoon commander is not quite optimum because there is still breaching in the battalion 405/Surya Kusuma. One of the problems is the lack of personnel and the number of assignments in this regard many members was doing BP - (under orders) - prepared for task force. Hence, environmental security problems associated with the battalion barrier are severely damaged. The efforts which was made by Pletoon Commanders include: increasing pletoon commanders’ persuasiveness in order to make the members subservient to the commands and instructions given, holding the Commander's Hour, conducting united mental coaching / mental coaching of command, increasing religious activities, inviting legal expertise, giving the members chances to follow educations, and also applying the reward and punishments system more firmly. All members get the same rights in law enforcement discipline.